Individualised care and the professional practice environment: nurses’ perceptions - Katajisto, Jouko; Suhonen, Riitta; Charalambous, Andreas; Valimaki, Maritta; Leino-Kilpi, Helena (My University, 2010)
AIM: To describe individualised care and the professional practice environment from nurses' point of view and to explore the associations between them. BACKGROUND: There is an increasing emphasis on individualised nursing care within the literature and the health-care context. Preliminary evidence suggests that the implementation of individualised care is associated with the practice style of care, work organization and the practice environment. METHODS: An exploratory correlational survey was used. Data were collected using the Individualised Care Scale and Revised Professional Practice Environment instruments from nurses and nurse managers (n=207, response rate 59%) working in in-patient wards of three acute hospitals' 13 different units in Finland in 2008. Data were analysed based on descriptive statistics and Spearman's rho correlations. FINDINGS: Nurses perceived that they generally support patient individuality and that the care they provided was individualised. Nurses' perceptions about the support of individuality and views on individuality of care provided were associated with handling conflict, work motivation, control over practice, leadership and autonomy, relationships with physicians and cultural sensitivity. DISCUSSION: The findings support the perception that individualised care and the professional practice environment are associated. There is a need for further studies to examine these associations more closely. Manipulating aspects of the environment may possibly be used to increase the ability of the nurses to provide individualised care. Patient perspectives should be included in future studies. Because of the national data, the results are indicative only. CONCLUSIONS: The recognition of the associations between individualised care and professional practice environment elements may help to develop individualised clinical nursing care.
Keywords: Finland; Survey; Questionnaires; Individualism